Disease and discrimination : poverty and pestilence in colonial Atlantic America - Hutchinson, Dale L. (University Press of Florida, 2017)
Disease and discrimination are processes linked to class in the early American colonies. Dale Hutchinson argues that most colonists, slaves, servants, and nearby Native Americans suffered significant health risks due to their lower economic and social status. Hutchinson posits that poverty and living conditions, more so than microbes, were often at the root of epidemics.